Thyroid Function Within the Normal Range, Subclinical Hypothyroidism, and the Risk of Atrial Fibrillation. Issue 22 (28th November 2017) - Baumgartner, Christine; da Costa, Bruno R.; Collet, Tinh-Hai; Feller, Martin; Floriani, Carmen; Bauer, Douglas C.; Cappola, Anne R.; Heckbert, Susan R.; Ceresini, Graziano; Gussekloo, Jacobijn; den Elzen, Wendy P.J.; Peeters, Robin P.; et al.
Abstract : Background: Atrial fibrillation (AF) is a highly prevalent disorder leading to heart failure, stroke, and death. Enhanced understanding of modifiable risk factors may yield opportunities for prevention. The risk of AF is increased in subclinical hyperthyroidism, but it is uncertain whether variations in thyroid function within the normal range or subclinical hypothyroidism are also associated with AF. Methods: We conducted a systematic review and obtained individual participant data from prospective cohort studies that measured thyroid function at baseline and assessed incident AF. Studies were identified from MEDLINE and EMBASE databases from inception to July 27, 2016. The euthyroid state was defined as thyroid-stimulating hormone (TSH) 0.45 to 4.49 mIU/L, and subclinical hypothyroidism as TSH 4.5 to 19.9 mIU/L with free thyroxine (fT4) levels within reference range. The association of TSH levels in the euthyroid and subclinical hypothyroid range with incident AF was examined by using Cox proportional hazards models. In euthyroid participants, we additionally examined the association between fT4 levels and incident AF. Results: Of 30 085 participants from 11 cohorts (278 955 person-years of follow-up), 1958 (6.5%) had subclinical hypothyroidism and 2574 individuals (8.6%) developed AF during follow-up. TSH at baseline was not significantly associated with incident AF in euthyroid participants or those with subclinical hypothyroidism. Higher fT4 levels at baseline in euthyroid individuals were associated with increased AF risk in age- and sex-adjusted analyses (hazard ratio, 1.45; 95% confidence interval, 1.26–1.66, for the highest quartile versus the lowest quartile of fT4; P for trend ⩽0.001 across quartiles). Estimates did not substantially differ after further adjustment for preexisting cardiovascular disease. Conclusions: In euthyroid individuals, higher circulating fT4 levels, but not TSH levels, are associated with increased risk of incident AF. Abstract : Supplemental Digital Content is available in the text.